Customary or Religious Law: Unregistered Marriage and Its Relationship to Joint Property - Mahmudin Mahmudin; Muhammad Hamid Bahamish (PT. Global Pustaka Ilmiah, 2025)
This research aims to analyze the legal impact of unregistered marriages in relation to the ownership of joint property, as well as consider the pretexts of customary and religious law that are often used to justify the practice. Using the normative juridical research method, this study examines legal theories, legal principles, and legislation related to marriage and property division in Islamic law and state law. The results show that the pretext of customary and religious law in unregistered marriages creates legal complexity, both in customary law and in state law. To regulate marriage registration, the ijtihad insya'i approach can be applied with the principle of “rejecting harm takes precedence over bringing good.” This approach requires the support of Indonesian Muslim scholars and thinkers to raise public awareness about the importance of marriage registration in the civil aspect and ownership of joint property. In addition, although in customary law joint property is often divided equally, in practice judges may consider the principle of justice based on the facts at trial. Therefore, education by state authorities and ulama is necessary to raise legal awareness in the community towards marriage registration.